Agroforestri Sebagai Upaya Peningkatan Produktivitas Lahan di Desa Kayu Aro - Abdan Syakura; Ramadana Hafizah; Aflah Rayhandi Nofri; Dina D; Husniyah Muna Arifin; Imelda Mahanani; Jihan Fadillah; Marsanda Wandari Putri; Wahyu Tegar Pratama; Wisami Syarifah Tara (Yayasan Daarul Huda Kruengmane, 2026)
Community Service Program (Kuliah Kerja Nyata/KKN) is one of the implementations of the Tri Dharma of Higher Education aimed at integrating education, research, and community service to assist rural development. Kayu Aro Village, Kampar Utara District, Kampar Regency, has considerable potential in the agricultural sector, which serves as the primary livelihood of the local community. However, land management is still predominantly based on monoculture systems, resulting in less optimal land productivity and limited long-term economic benefits. Therefore, the 2026 Community Service Program of Universitas Riau implemented an agroforestry program by iintegrating forestry crops, namely durian (Durio zibethinus) and jengkol (Archidendron pauciflorum), with maize (Zea mays) using a boundary planting pattern. The iprogram was conducted from 18 July 2026 through coordination, socialization, extension activities, group discussions, seedling distribution, and direct planting practices. A total of 150 seedlingsi consisting of 75 durian seedlings and 75 jengkol seedlings were distributed to the Srikandi Farmer Group and Hijrah Lestari Farmer Group. The seedlings were planted along the boundaries of maize fields, allowing the annual crops to grow without disrupting maize cultivation while providing long-term ecological and economic benefits. The implementation showed positive community participation and improved public understanding regarding sustainable agroforestry practices. This program is expected to enhance land productivity, improve environmental quality, reduce land degradation, and support sustainable land management in Kayu Aro Village.